AI-Powered Assistive Technologies for Improved Accessibility - Brotosaputro, Goenawan; Supriyadi, Agung; Jones, Michael (International Transactions on Artificial Intelligence, 2024)
This research explores the effectiveness of AI-powered assistive technologies in enhancing accessibility for individuals with disabilities. The study combines qualitative and quantitative methods to evaluate the usability, efficiency, and user satisfaction of AI-integrated solutions compared to traditional assistive technologies. Findings indicate significant improvements in these areas, with AI-powered technologies reducing task completion times and increasing user satisfaction and communication efficiency. Case studies highlight diverse applications, such as AI-driven speech recognition and emotion recognition systems, demonstrating substantial benefits. Despite the promising results, the study acknowledges limitations such as small sample size and short-term focus, suggesting future research to explore long-term impacts, cost-effectiveness, and broader accessibility. This research contributes to the field of accessibility by providing empirical evidence of AI transformative potential, emphasizing the importance of personalized and adaptive support. Future developments should ensure sustainable and equitable implementation to maximize the benefits of AI-powered assistive technologies.